Persepsi Auditor terhadap Perubahan Pengakuan Pendapatan dalam Transisi SAK ETAP ke SAK EP - Rian Emon Ginting; Mohammad Iqbal Firdaus (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2026)
This study aims to examine the differences in revenue recognition between SAK ETAP and SAK EP, while also exploring auditors' perceptions of the accompanying transformation in audit practices. This transition reflects the development from a transaction-based orientation, through a risk and reward approach, to a performance obligation framework, a trajectory that carries significant implications for increasing audit complexity. Using a qualitative methodology supported by descriptive analysis, data were collected through semi-structured interviews with auditors from selected Public Accounting Firms (KAP), identified through purposive sampling. Thematic analysis was conducted through systematic data reduction, structured presentation, and interpretive inference, thus elucidating important conceptual patterns and themes. The findings indicate that auditors generally understand the conceptual shift in revenue recognition, although the depth of understanding depends on professional experience. The adoption of SAK EP has been shown to increase audit complexity, particularly regarding contract interpretation and the timing of revenue recognition, while also strengthening reliance on professional judgment. However, ongoing challenges remain, including limited human resources, limited organizational readiness, and deficiencies in information systems. Despite these challenges, auditors agree that SAK EP enhances the transparency and qualitative robustness of financial reporting. The implications of this study underscore that the successful institutionalization of SAK EP depends not only on auditor adaptability but also on entity readiness. Therefore, continued investment in competency development, targeted training, and adequate information system enhancements are crucial. Further research is recommended to expand the scope of informants and complement qualitative insights with quantitative assessments of the impact of SAK EP implementation.